Tim-3 Expression Causes NK Cell Dysfunction in Type 2 Diabetes Patients - Wang, Hui; Cao, Kangli; Liu, Siyu; Xu, Yuanhong; Tang, Ling (Frontiers in Immunology, 2022)
Type 2 diabetes mellitus (T2DM) is characterized by high blood glucose levels and chronic low-grade inflammation. It shows a strong association with obesity and immune dysfunction, which makes T2DM patients more susceptible to infectious diseases. NK cells play an important role in pathogen control and tumor surveillance. However, whether NK cell distribution and functional status are altered in T2DM is unclear. To address this issue, we compared surface receptor expression and cytokine production between peripheral blood NK cells from 90 T2DM patients and 62 age- and sex-matched healthy controls. We found a significantly lower frequency and absolute number of NK cells in patients than in controls. Interestingly, the expression of inhibitory receptor Tim-3 was significantly increased, while the expression of the activating receptor NKG2D was significantly decreased, in T2DM NK cells. Both TNF-α secretion and degranulation capacity (evidenced by CD107a expression) were dampened in NK cells from patients. The expression of Tim-3 on NK cells correlated positively with both HbA1c and fasting blood glucose levels and negatively with the percentage and absolute number of total NK cells and was associated with increased NK cell apoptosis. In addition, Tim-3 expression on NK cells negatively correlated with TNF-α production, which could be restored by blocking Galectin-9/Tim-3 pathway. Our results suggest that NK cell dysfunction secondary to augmented Tim-3 expression occurs in T2DM patients, which may partly explain their increased susceptibility to cancer and infectious disease.